Isolation and Characterization of Multipotent CD24+ Cells From the Renal Papilla of Swine - Burmeister, David M.; McIntyre, Matthew K.; Montgomery, Robbie K.; Gómez, Belinda I.; Dubick, Michael A. (Frontiers in Medicine, 2018)
Over 100,000 patients in the United States are currently waiting for a kidney transplant. With just over 10,000 cadaveric kidneys transplanted annually, it is of the utmost importance to optimize kidney viability upon transplantation. One exciting avenue may be xenotransplantation, which has rejuvenated interest after advanced gene editing techniques have been successfully used in swine. Simultaneously, acute kidney injury is associated with high morbidity and mortality and currently lacks effective treatment. Animal models have been used extensively to address both of these issues, with recent emphasis on renal progenitor cells. Due to anatomical similarities to humans we aimed to examine progenitor cells from the renal papillae of swine kidneys. To do this, renal progenitor cells (RPCs) were dissected from the renal papillae of healthy swine. Cell surface marker expression, proliferation, and differentiation of the RPCs were tested in vitro. Additionally, a mixed lymphocyte reaction was performed to examine immunomodulatory properties. RPCs displayed spindle shaped morphology with limited self-renewing capacity. Isolated RPCs were positive for CD24 and CD133 at early passages, but lost expression with subsequent passaging. Similarly, RPCs displayed myogenic, osteogenic, and adipogenic differentiation capacities at passage 2, but largely lost this by passage 6. Lastly, direct contact of RPCs with human lymphocytes increased release of IL6 and IL8. Taken together, RPCs from the papilla of porcine kidneys display transient stem cell properties that are lost with passaging, and either represent multiple types of progenitor cells, or a multipotent progenitor populaiton. In instances of ischemic insult, augmentation of/with RPCs may potentiate regenerative properties of the kidney. While the use of swine for transplantation and ischemia studies confers obvious advantages, the populations of different progenitor cell populations within pig kidneys warrants further investigation. Ultimately, while gene editing techniques enhance the potential for xenotransplantation of organs or cells, the ultimate success of this strategy may be determined by the (dis)similarities of RPCs from different species.